The Relationship of Job Satisfaction with the Performance of University Faculty in Azad Jammu & Kashmir - Zia, Asma Zia; Adeel Ahmed Khan,; Rabia Khurshid, (JCTE, 2024)
Job satisfaction has a direct link with the performance of workers in an institution. Satisfied teachers with their job responsibilities perform better in their educational institutions. The purpose of this study was to determine the relationship between university faculty performance in Azad Jammu & Kashmir and job satisfaction. The correlation design was used in this quantitative investigation. Using a random sampling procedure, 541 academic staff members from Azad Jammu & Kashmir's five public universities were chosen. To obtain data, a self-structured questionnaire was employed. The findings of the study showed that there is a positive correlation between job satisfaction and performance among university faculty, although the relationship is relatively weak.